Perencanaan Jaringan Fiber To The Home (FTTH) Berdasarkan Jaringan Telepon Existing Di Kampus Universitas Riau(UR) Panam - Awaluddin, Muhammad; Febrizal, Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper discusses about fiber to the home network (FTTH) at panam riau university campus. In designing, it is required to determine the closest STO, and the determination of the distribution channels. The analysis of designing will involve two parameters.i.e. power link budget, and rise time budget. The result of power link budget shows a maximum of -27 dBm receiver sensitivity. In the meantime the downlink an uplink total calculation is considered acceptable to conduct the NRZ encoding due to remains within the specification of downlink and uplink bitrate total time.i.e. 0,562 ns and 0,2813 ns, respectively. In overall, it is indicated that the link budget and the rise time budget is complied to NRZ encoding requierementKeywords : University of Riau, FTTH, Power Link Budget, Rise Time Budget